2012
DOI: 10.4236/ojss.2012.24042
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties of a Tropical Savannah in the Eastern Ghats of India

Abstract: As an outcome of globalization and liberalization of economic policies, exploration for and mining of minerals have become one of the recent lucrative trades in India. Due to stringent environment legislations, reclamation and reforestation of the mined out sites have become obligatory. Information on distribution of nutrients before and after mining provides valuable insights while developing and executing the strategy for reclamation and revegetation of the mined out sites. Successful mine reclamation plan c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Soil reaction is prime importance in controlling the availability of nutrients, since it affects directly their solubility as well as activity in the soil environment. The similar results were obtained at another palace by Chandra et al (2012) [5] , Mukherjee and Lal (2014) [17] and Cherubin et al (2016) [6] .…”
Section: Discussionsupporting
confidence: 86%
“…Soil reaction is prime importance in controlling the availability of nutrients, since it affects directly their solubility as well as activity in the soil environment. The similar results were obtained at another palace by Chandra et al (2012) [5] , Mukherjee and Lal (2014) [17] and Cherubin et al (2016) [6] .…”
Section: Discussionsupporting
confidence: 86%
“…Iron oxide has a correlation of 0.5 with P. OM has positive correlation of 0.2 and 0.1 with P and K respectively. whereas, Chandra et al (2012) observed a correlation of 0.25. Positive correlation of 0.2 is observed between pH and P (Chandra et al, 2012).…”
Section: Correlation Between Topsoil Chemical Propertiesmentioning
confidence: 89%
“…whereas, Chandra et al (2012) observed a correlation of 0.25. Positive correlation of 0.2 is observed between pH and P (Chandra et al, 2012). EC and Ca have positive correlation of 0.3 (Chaudhari et al, 2012).…”
Section: Correlation Between Topsoil Chemical Propertiesmentioning
confidence: 89%